Carbon and Nitrogen in Forest Ecosystems-Series I - Son, Yowhan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Understanding the differences in carbon and nitrogen distribution and cycling both spatially and temporally using various approaches is essential in forest ecosystems. In addition, the influence of biotic and abiotic factors as well as natural and artificial disturbances on carbon and nitrogen cycling need to first be understood before drawing their implications to forest management practices. This Special Issue aims to understand carbon and nitrogen distribution and cycling in forest ecosystems for ecosystem-based forest management under different natural and artificial disturbances.